Impact of ICT in Oil and Gas Exploration: A Case Study - Ike, Dike U.; Anthony, Adoghe; Anthony, Adoghe; Abdulkareem, Ademola; Abdulkareem, Ademola (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Information and Communication Technology (ICT) is of great importance to almost all aspects of oil and gas operations, from upstream to downstream operations. ICTs help to optimize oil and gas processes and thus improves Â the efficiency and viability of oil and gas operations. This paper presents the core areas of application of ICTs in the oil and gas industry using Nigeriaâ€™s oil and gas industry as a case study.